Computer Anxiety Dan Computer Attitude Pada Computer Self Efficacy Mahasiswa Dalam Menggunakan Accurate - Ni Komang Urip Krisa Dewi; Ni’immas Ni’immas (EBBANK, 2022)
The purpose of this study is to determine the effect of computer anxiety and computer attitude to computer self efficacy in using accurate. This study use survey metode with questinnaire technique for data collection and analysis techniques of multiple linear regression which includes classical assumption and hypothesis testing using partial test and coefficient of determination. Based on the analysed data the results obtain are as follows, computer anxiety effect negatively, computer attitude effect positively, experience effect positively